A cytorhabdovirus phosphoprotein forms mobile inclusions trafficked on the actin/ER network for viral RNA synthesis. (25th April 2019) - Fang, Xiao-Dong; Yan, Teng; Gao, Qiang; Cao, Qing; Gao, Dong-Min; Xu, Wen-Ya; Zhang, Zhen-Jia; Ding, Zhi-Hang; Wang, Xian-Bing
Abstract: As obligate parasites, plant viruses usually hijack host cytoskeletons for replication and movement. Rhabdoviruses are enveloped, negative-stranded RNA viruses that infect vertebrates, invertebrates, and plants, but the mechanisms of intracellular trafficking of plant rhabdovirus proteins are largely unknown. Here, we used Barley yellow striate mosaic virus (BYSMV), a plant cytorhabdovirus, as a model to investigate the effects of the actin cytoskeleton on viral intracellular movement and viral RNA synthesis in a mini-replicon (MR) system. The BYSMV P protein forms mobile inclusion bodies that are trafficked along the actin/endoplasmic reticulum network, and recruit the N and L proteins into viroplasm-like structures. Deletion analysis showed that the N terminal region (aa 43–55) and the remaining region (aa 56–295) of BYSMV P are essential for the mobility and formation of inclusions, respectively. Overexpression of myosin XI-K tails completely abolishes the trafficking activity of P bodies, and is accompanied by a significant reduction of viral MR RNA synthesis. These results suggest that BYSMV P contributes to the formation and trafficking of viroplasm-like structures along the ER/actin network driven by myosin XI-K. Thus, rhabdovirus P appears to be a dynamic hub protein for efficient recruitment of viral proteins, thereby promoting viral RNA synthesis. Abstract : A cytorhabdovirus phosphoprotein forms mobile inclusion bodies that traffic along the actin/endoplasmic reticulum network in a process that is important for viral RNA synthesis.